2020
DOI: 10.1371/journal.pone.0237869
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt dietary changes between grass and hay alter faecal microbiota of ponies

Abstract: Abrupt dietary changes, as can be common when managing horses, may lead to compositional changes in gut microbiota, which may result in digestive or metabolic disturbances. The aim of this study was to describe and compare the faecal microbiota of ponies abruptly changed from pasture grazing ad libitum to a restricted hay-only diet and vice versa. The experiment consisted of two, 14-day periods. Faecal samples were collected on day 0 and days 1-3,7,14 after abrupt dietary change from grass to hay and from hay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
2
14
0
Order By: Relevance
“…Firmicutes and Bacteroidetes dominated the faecal bacterial profiles of healthy horses in the present study, as previously reported in our work [ 15 , 33 ] and several other equine microbiota studies [ 12 , 16 , 21 , 52 , 53 ]. Members of the phyla Firmicutes and Bacteroidetes are anaerobic cellulolytic bacteria associated with fibre digestion, and many of the bacterial genera within these phyla thrive on fermentable carbohydrates [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firmicutes and Bacteroidetes dominated the faecal bacterial profiles of healthy horses in the present study, as previously reported in our work [ 15 , 33 ] and several other equine microbiota studies [ 12 , 16 , 21 , 52 , 53 ]. Members of the phyla Firmicutes and Bacteroidetes are anaerobic cellulolytic bacteria associated with fibre digestion, and many of the bacterial genera within these phyla thrive on fermentable carbohydrates [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
“…Under these management systems, horses may undergo abrupt dietary changes, with the incorporation of grains or concentrate feeds to the diet to meet performance needs, or sudden changes in the type of forage fed in response to a lack of fresh or conserved forage [ 9 ]. Abrupt changes in dietary management are a risk factor for gastrointestinal (GI) disturbances, potentially due to the negative effects observed on the population of GI microbiota [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in Sarcina across the W–C transition in CRS were also reflected in the genus-level analysis in addition to fluctuation in Bacillus for the W–C in BRS. Garber et al [ 34 ] also found Sarcina enriched in horses transitioning to cool-season grass from a hay diet. These results indicate that taxa represented by these ASV, and the Sarcina and Bacillus genera more broadly, may be more sensitive to subtle changes in pasture forage type and nutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in New Zealand, specific taxa were identified to be more abundant in horses abruptly transitioned to pasture: an unclassified genus within the order of Clostridiales, an unclassified genus within the order of Lachnospiraceae, CF231 and BF311 [9]. Another recent study reported an increase in Lactobacillaceae in horses that were abruptly changed from a hay-only diet to a grass diet [54]. The horses included in our study did not undergo abrupt dietary changes and had the same level of pasture access over a prolonged period prior to sampling, which might explain the differences observed when the results of our study are compared to that of previous reports.…”
Section: Pasture Accessmentioning
confidence: 99%